Folk military songs through the prism of tragic and heroic categories (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article analyzes the problem of reflecting in Cossack and soldiers' folk songs the perceptions of the tragedy and heroism. This paper focuses on transforming the ethical and aesthetic concept of a national hero from the «national moral code» active social person (Cossack as an ideal character) to a passive acting individual in the state and society life. Cossack death representation deals with interpreting military activities as important needs dictated by national demands of «heroic» era. It is depicted as the natural result of the active and dynamic life and person's conscious readiness for sacrificing. The tragic nature of this phenomenon in the folk songs is achieved due to new ethical and aesthetic features caused by percepting Cossacks the special role of a person in society, individual moral responsibility and patriotism aesthetics. Recruiting and soldier death perception is formed by means of certain attitude to military service as disharmonious, illogical, unnatural, unnecessary activity.
Keywords: Cossack; recruit; soldier; tragic; heroic